PWE-027 The Reasons For Gender Differences In Caecal Intubation Rates – Analysis Of 8324 Colonoscopies Over 6 Years. (9th June 2014) - Verma, AM; Smith, RE; McGrath, N; Dixon, A; Chilton, AP
Abstract : Introduction: In 2012 we presented a poster to the Digestive Disorders Foundation Meeting, we analysed 5162 colonoscopies and noted a significant difference in caecal intubation rates (CIR) of male and female patients (92.73% v 87.63%, p < 0.0001, NNH 19.57). 1 Gender differences in colonoscopy have been published previously in the 1990s. 2, 3 Several theories were mooted for this difference; such as female patients undergoing previous hysterectomy, 2 and having longer colons. 3 We have revisited this topic to identify causes of the difference relevant to modern colonoscopic practice. Methods: Data was analysed from 8324 colonoscopies at Kettering General Hospital 2008–13. Incomplete colonoscopies' reports were scrutinised to record the causes of failure. Results: Reason for failed colonoscopy (females v males, p value) Poor bowel preparation (16.38 vs. 24.66%, 0.09), tight bend (6.21 vs. 0.91%, <0.03) Intolerance/pain (27.97 vs. 19.63%, 0.11), looping (18.36 vs. 18.72%) Obstructing lesion (8.19 vs. 15.53%, 0.06), previous surgery (5.37 vs. 0.46%, <0.03) Diverticular disease (9.32 vs. 5.02%, 0.18), withdrew consent (5.93 vs. 2.28%, 0.14) Conclusion: The data reveals significant differences in CIR between female and male patients (90.89 vs. 95.07%, p < 0.0001, NNH 24). Analysis of the reasons recorded for failure shows a strong trend in males for poor bowel preparation and obstructing lesion. In females, a strong trend was shown for pain/intolerance, diverticular disease and withdrawal of consent. Statistical significance was shown for previous (abdominal) surgery and tight bend. Looping is a common reason for failing colonoscopy with no gender difference. This is an important observation that females are significantly less likely to have complete colonoscopy. Perhaps endoscopy units should outline the potential for missed lesions as a consequence when consenting female patients – in particular those with known diverticular disease or previous abdominal surgery. Other reasons of failure could also be addressed e.g. higher doses of analgesia for females as required. References: 1 Verma AM, McGrath N, Dixon A, Chilton AP. Gender differences: analysis of 5162 colonoscopies over 4 years reveals higher caecal intubation rates in male patients. Gut 2012;61:Suppl 2 A150-A151 2 Church JM. Complete colonoscopy: How often? And if not, why not? Am J Gastroenterol 1994;89:556–60. 3 Saunders BP, Fukumoto M, Halligan S, et al . Why is colonoscopy more difficult in women? Gastrointestinal Endoscopy 1996;43:124–6. Disclosure of Interest: None Declared.